Examen especial a los activos corrientes de servicios educativos eduinternacional Cía. Ltda., Sedei, de la ciudad de Loja período enero-junio 2016 - Pérez González, María Gabriela (2017)
The subject of investigation that was made with the purpose of fulfilling one of the prerequisites to the degree of Engineering in Accounting and Auditing C.P.A., and that the results obtained in this work, are of fundamental contribution for the improvement of the company with education services, which it was developed subject to the Ecuadorian Auditing Standards, Internal Control Standards and Generally Accepted Accounting Principles. I can say that to analyze the researched accounts as they are: general cash, banks, advances to suppliers and salary advances to employees; it began with the first phase of “Planning” where the objectives were established, and in a preliminary way the strategy to be followed in the process was organized. In the second phase, “Work Execution” inquiring the sufficient information and applying tests and auditing practices with the purpose to examine the selected accounts and finally the “Communication of the Results” by writing the respective report with its respective conclusions and recommendations In conclusion, and after finishing the Special Examination to an education services company, I discovered that in SEDEI, weaknesses were found in the management and control specifically in the accounts of General Cash and Advances to Suppliers, by the untimely intervention of the personnel of the accounting department (General Cashier) and Manager with regard to (advances to suppliers); recommending Surprise Cash Counts and carry out properly the delivery of Advances to Suppliers with supporting documents.